PENGARUH PERASAN BUAH AIR NANAS (ANANAS COMOCUS L. MERR) SEBAGAI KOAGULAN LATEKS DI DESA HILIONAHA KECAMATAN ONOLALU KABUPATEN NIAS SELATAN”. - Mistariani Gowasa (Universitas Nias Raya, 2023)
This study was conducted in Hilionaha Kecamata Onolalu Village starting from June 9-30, 2021. This study aims to determine the influence of pineapple water squeeze as a coagulant in freezing latex. This type of research is quantitative research with experimental or quasi-experimental (True Eksperiment) with a Complete Randomized Design (RAL) experimental design. The population of this study was as many as 25 rubber trees (Havea brasiliiensis). The sample of this study was Purposive sampling consisting of 25 beaker glass latex. The data on the study were analyzed using the SPPS 20 application consisting of the Normality Test, Homogeneity Test, Hypothesis Test and Advanced Test. The findings of the study with the administration of pineapple water as coagulants affect the freezing of rubber sap. Then it can be concluded that pineapple water juice can be used as a coagulant material in freezing latex. The advice offered by researchers, should the use of pineapple water squeeze as a cane can be applied and able to improve the quality of agriculture and help improve the economy of rubber farmers.